Faktor-faktor yang Mempengaruhi Prestasi Mahasiswa Ditinjau dari Karakteristik Lingkungan Kampus (Studi Kasus di Jurusan Matematika FMIPA Unsri) - Oki Dwipurwani; Sri Indra Maiyanti; Anita Desiani; Sari Suryati (Faculty of Mathtmatics and Natural Sciences, 2012)
This Research aim to develop a model which can explain factors influencing student achievement. Variables in this research in the form of laten variable and causal relationship between a set of variables nor modestly, there is direct and indirectly relationship. Therefore, there used a Structural Equation Models (SEM) analyse method. Data in this research is obtained by through questionnaire from Mathematics FMIPA Unsri Majors student sample as much 128 responder. Result of analysis indicate that student perception to dosen variable have an positive effect directly to student motivation variable as well as having an positive effect indirectly through motivation variable to achievement variable which signifikan that is each equal to 0.46 and 0.4784. Furthermore, motivate to learn variable have an positive effect to student achievement variable equal to 1,04.